NORMS FOR DESTRUCTIVE BENDING MOMENTS OF T-SHAPE CORNER JOINTS OF FRAME STRUCTURAL ELEMENTS MADE OF SOLID SPRUCE WOOD WITH A CROSS-SECTION OF 50 х 30 mm (Innovation in Woodworking Industry and Engineering design, 2026)
In the presented research are established the normative values for the destructive bending moments of the most common used T-shape corner joints of frame structural elements made of solid spruce wood with a cross-section of 50 х 30 mm in arm compression bending load. The established normative values can be used for the needs of the preventive quality control of furniture production as well as for the strength design of the sitting furniture, tables, and beds. For that purpose, it is recommended to draw up these normative values as a normative document which to use in the inner factory control of furniture quality.